Strengthening the Protection for Women and Children from Violence: (Collaboration between Aisyiyah and Nasyiatul Aisyiyah in Sorong) - Mardliyah, Uswatul; Rais, Lukman; Rumodar, Rosniati (Jurnal Perempuan dan Anak, 2024)
This research aims to analyze: 1) Aisyiyah and Nasyiatul Aisyiyah programs in helping women and children at risk of being exposed to violence, 2) The role of religious approaches in the collaboration between Aisyiyah and Nasyiatul Aisyiyah in protecting women and children from violence, 3) Challenges and obstacles faced in overcoming violence against women, and 4) The positive impact of the collaboration between Aisyiyah and Nasyiatul Aisyiyah in efforts to protect women and children from violence. The type of research used is qualitative with a phenomenological design, conducted in Sorong City, Southwest Papua Province, from March to May 2024. The research results show that in Sorong City, Aisyiyah and Nasyiatul Aisyiyah are actively involved in programs to help women and children at risk of being exposed to violence. However, this involvement is limited due to the lack of an integrated service center, leading to a recommendation for the immediate creation of such a center to comprehensively assist victims of violence. Furthermore, the religious approach plays an important role in the collaboration between Aisyiyah and Nasyiatul Aisyiyah in protecting women and children from violence in Sorong City. As part of Muhammadiyah, these two organizations adopt an approach based on Islamic religious values in carrying out their programs. In addressing violence against women in Sorong City, West Papua, there are several complex challenges, including violence rooted in culture and customs, as well as social stigma.